Understanding wood a craftsman's guide to wood technology - Hoadley, R. Bruce 1933-; O'Rourke, Randy; Starr, Richard; Robinson, Charley; Waters, Alec; Laurence, Vincent; Ferro, Mario (Newtown, CT Taunton Press ; [Emeryville, CA] : Publishers Group West [distributor], 2000)
"Understanding Wood is updated to include new information on composite materials, adhesives, and finishes developed in the past 20 years. R. Bruce Hoadley explores the nature of wood and its properties, the basics of wood technology, and the woodworker's raw materials. You'll learn the best ways to cut, season, machine, join, bend, fasten, and finish wood, and explore the crucial interaction of wood and moisture. You'll also find the latest on wood products and where to buy them."--BOOK JACKET
The Nature of Wood -- Figure in Wood -- Wood Identification -- Strength of Wood -- Other Properties of Wood -- Water and Wood -- Coping with Dimensional Changes in Wood -- Drying Wood -- Machining and Bending Wood -- Joining Wood -- Adhesives and Gluing -- Finishing and Protecting Wood -- Lumber -- Veneer and Plywood -- Composite Panels -- Engineered Wood -- Finding Wood.
Includes bibliographical references and index (pages 272-280).
Keywords: Woodwork; Wood